The effects of midodrine on the natriuretic response to furosemide in cirrhotics with ascites - Misra, V. L. (2010)
BACKGROUND: Resistance to loop diuretics is common in patients with ascites. Diminished glomerular filtration rate (GFR) is thought to mediate resistance to loop diuretics. Midodrine, a commonly used alpha-1 agonist, has been shown to improve GFR in non-azotemic patients with cirrhosis. AIM: To conduct a randomized, double-blind, placebo-controlled, cross-over study to test the hypothesis that midodrine significantly increases natriuretic response of IV furosemide in non-azotemic cirrhotics with ascites. METHODS: All subjects participated in both phases, which were (i) furosemide IV infusion + oral midodrine 15 mg administered 30 min before furosemide (ii) furosemide IV infusion + oral placebo administered 30 min before furosemide. Primary outcomes were 6-h urine sodium excretion and 6-h total urine volume. RESULTS: A total of 15 patients (men: 8; age: 52.7 ± 7.6 years; serum creatinine: 1.06 ± 0.2 mg/dL) were studied. Total 6-h urine sodium excretion was 109 ± 42 mmol in the furosemide + midodrine treatment phase and was not significantly different from that in the furosemide + placebo treatment phase (126 ± 69 mmol, P = 0.6). Similarly, mean 6-h total urine volume was not significantly different between two groups (1770 ± 262 mL vs. 1962 ± 170 mL, P = 0.25). CONCLUSIONS: Oral midodrine does not increase the natriuretic response to furosemide in non-azotemic cirrhotic patients with ascites. Orally administered midodrine does not increase natriuretic response to furosemide in non-azotemic cirrhotic patients with ascites.